Comparative cytotoxic study of silica materials functionalised with essential oil components in HepG2 cells. (January 2021) - Fuentes, Cristina; Ruiz-Rico, María; Fuentes, Ana; Barat, José Manuel; Ruiz, María José
Abstract: This work evaluated the cytotoxic effect of different EOCs-functionalised silica particle types. The in vitro toxicity of eugenol and vanillin-immobilised SAS, MCM-41 microparticles and MCM-41 nanoparticles was evaluated on HepG2 cells, and compared to free EOCs and pristine materials. The results revealed that free essential oil components and bare silica had a mild cytotoxic effect on HepG2 cells. However, the comparative study showed that free eugenol and vanillin had a milder cytotoxic effect than the equivalent concentrations of immobilised components on the different silica particles, while differences in cell viability between the bare and functionalised particles relied on the type of analysed material. The most cytotoxic materials were eugenol and vanillin-functionalised MCM-41 micro with IC50 values of 0.19 and 0.17 mg/mL, respectively, at 48 h exposure. Differences in cytotoxicity between functionalised particles may be attributed to the density of the functional components on their surface as a result of the functionalisation reaction performance for different materials. The study of the physico-chemical properties of particles demonstrated that cationic nature and increased hydrophobicity could be responsible for promoting cell-particle interactions for the eugenol and vanillin functionalised silica particles, enhancing their cytotoxic behaviour. Graphical abstract: Image 1 Highlights: Cytotoxicity of new antimicrobial systems for food applications was evaluated. Functionalised silica was more cytotoxic than EOCs and bare MCM-41 particles. Functionalised MCM-41 microparticles were the most cytotoxic material. Differences in cytotoxicity between particles relied on functionalisation yield. Functionalised silica cytotoxicity may depend on enhanced cell-particle interaction.